Multinational enterprises, international trade, and productivity growth: Firm-level evidence from the United States - Wolfgang Keller; Stephen R. Yeaple (Brown University, Department of Economics, 2003)
We estimate international technology spillovers to U.S. manufacturing firms via imports and foreign direct investment (FDI) between the years of 1987 and 1996. In contrast to earlier work, our results suggest that FDI leads to significant productivity gains for domestic firms. The size of FDI spillovers is economically important, accounting for about 14% of productivity growth in U.S. firms between 1987 and 1996. In addition, there is some evidence for imports-related spillovers, but it is weaker than for FDI. The paper also gives a detailed account of why our study leads to results different from those found in previous work. This analysis indicates that our results are likely to generalize to other countries and periods.
Keywords: 330; Multinationales Unternehmen; Produktivität; Direktinvestition; Technologietransfer; Spillover-Effekt; Schätzung; USA; Welt